Potensi Penggunaan Aplikasi dalam Pengurusan Keselamatan dan Kesihatan di Tapak Pembinaan - Mohd Sabri, Nurul Auni Najwa; Kai Chen, Goh; Shafii, Haryati (Research in Management of Technology and Business, 2021)
The use of safety and health applications in the management of safety and health at construction sites is a method to prevent accidents and ensure the safety of workers at construction sites is more secure. However, awareness and exposure to occupational safety and health (OSH) officers on the potential use of these safety and health applications is still low and underutilized in the construction sector in Malaysia. Therefore, the objective of this study is to identify OSH officers’ understanding of the potential use of safety and health applications for safety and health management at construction sites and to identify challenges in the use of safety and health applications for safety and health management at construction sites. The scope of the study focuses on OSH officers in the state of Selangor. The selection of the state of Selangor as the study area because of its area which is the focus of the construction sector. An allocation of almost RM7.35 billion for the construction sector around the state of Selangor. The research method used is qualitative which involves interviews with 3 respondents who are OSH officers who have experience in the use of safety and health applications. The data obtained were analyzed using content analysis method. The results of the study found that all three respondents agreed on the potential use of safety and health applications for safety management that can help minimize the risk of accidents at construction sites. The study also found that there are challenges in the use of safety and health applications is related to the role of individuals who use the applications. The use of safety and health applications among OSH officers has the potential to help facilitate the work of monitoring safety aspects at construction sites.